PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV DI SEKOLAH DASAR - Suryadin Hasyda; Arifin Arifin (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
The aim of this study is to improve students' critical thinking skills through a problem based learning model in class IV SDN Ende 1. The type of research used in this study is classroom action research consisting of several interrelated cycles and the model chosen in this study is a Kemis and Mc Tagart model which consists of several stages namely planning, action, observation and reflection, where actions and observations are carried out together. The subjects of this study were 21 students in class IV SDN Ende 1. Based on the results of data analysis in classroom action research shows that the learning feasibility by applying the learning model Problem Based Learning has increased namely 81.5% in the first cycle and 94% in the second cycle, therefore it can be said that the learning process has been carried out very well and in accordance with the reference in the lesson plan that has been made. While the results of observations of student activities during learning by applying  model of problem based learning have increased, which is proved by the increase in the average score of student learning activities in the first cycle by 55% and the second cycle by 87%. This improvement shows that during the learning process students were actively involved in solving problems. The results of the students’ critical thinking ability test of the first cycle can be seen that, there are 9 students or 43% who reach the KKM standard, while 12 students or 57% do not reach the value of 70 in accordance with the minimum completeness criteria set by the school. While the second cycle is known that as many as 21 students (100%) have succeeded and reached the indicator of critical thinking. The highest score obtained by student is 90 and the lowest score is 70 with an average value of 80% in the critical category. Therefore, the implementation of research by applying the problem based learning model ends in the second cycle . So, through research that has been done, by applying the Problem Based Learning model it is proven that it can improve the critical thinking skills of class IV students whose critical thinking test results are complete or meet the minimum completeness criteria (KKM).